Friction and wear behaviors of aircraft brake linings material - Celiktas, Erhan; Topuz, Ahmet; Kazanci, Zafer (EMERALD GROUP PUBLISHING LTD, 2012)
Purpose - The purpose of this paper is to produce and investigate a reliable and effective aircraft brake lining material. Design/methodology/approach - In total, four different Cu-based brake lining samples were produced by powder metallurgy. The produced samples were tested in an experimental setup on friction, wear and mechanical performance, then metallographic and scanning electron microscope inspections were performed. Hardness, compression strength and density of copper-based brake linings were also tested. Moreover, a numerical simulation of the structural reaction of a sample under compression was carried out by using ANSYS. Findings - According to tests, suitable aircraft brake lining material composition would be 75% Cu, 5% Fe, 5% Sn, 5% Graphite, 5% SiO2, 5% MoS2. Practical implications - The paper will help designers choose the most proper ingredient combination for aircraft brake lining materials. Originality/value - The paper notes that adding silicon dioxide and graphite forms a porosive structure. In addition, porosity brings a low strength and high wear rate.
Keywords: Aircraft components; Friction; Wear; Mechanical properties of materials; Cu-based brake linings; Powder metallurgy; PERFORMANCE; Engineering